The Effect Of Managerial Competence On The Performance Of Msmes Assisted By Business Incubators Through Digital Transformation As A Mediating Variable In Palu City - Arabila, Salwa Amelia; Mahardiana, Lina; Rossanty, Niluh Putu Evvy; Nugraha, Mohammad Ega (UNIVED Press, 2026)
This study aims to analyze the effect of managerial competence on the performance of MSMEs fostered by the Business Incubator in Palu City, with digital transformation as a mediating variable. The research employed a quantitative approach with an explanatory design involving 45 MSMEs selected through purposive sampling. Data were collected using questionnaires and analyzed with SEM-PLS through WarpPLS 7.0. The results indicate that managerial competence has a significant positive effect on MSME performance, while digital transformation has a significant negative effect and does not mediate the relationship. These findings highlight the importance of enhancing managerial competence to strengthen MSME performance in the digital era.